SOME REMARKS ON THE ADMINISTRATIVE CENTERS OF THE WESTERN TURKISH KHAKHANAT IN THE TASHKENT OASIS - Muhamedov Yoqubjon (Social science and innovation, 2023)
This article talks about the centers that performed the function of the administrative system during the period of the Western Turkic Khanate, in particular, the large cities in the Choch oasis and their activities.The information presented in the article is covered by mutual analysis of the information provided in archaeological and written sources.